An Unexpected C‐S Bond Transformation with High Chemoselectivity for the Synthesis of Aryl‐Benzyl Sulfones. Issue 33 (1st September 2021) - Liu, Teng; Shen, Xianfu; Liu, Zining; Shi, Rong; Wei, Wen; Xu, Yanli; Cheng, Feixiang
Abstract: In this report, an unexpected C−S bond transformation involving a high chemoselectivity between sulfonylhydrazides and dibenzyl phosphite catalyzed by NaI under mild conditions has been developed. This alternative protocol could provide a metal‐free route to access a diverse aryl‐benzyl sulfones in good to excellent yields. Abstract : In this report, an unexpected C−S bond transformation involving a high chemoselectivity between sulfonylhydrazides and dibenzyl phosphite catalyzed by NaI under mild conditions has been developed. This alternative protocol could provide a metal‐free route to access a diverse aryl‐benzyl sulfones in good to excellent yields and with high chemoselectivity.